PLANT COLLECTION IN BOGOR BOTANICAL GARDEN AS A SOURCE OF FUNCTIONAL FOOD - Hidayat, Syamsul (Media Konservasi, 2021)
Plant collection in Bogor Botanical Garden (BBG) has various potentials, one of which is as a food source. However, not all food produced from plants can be claimed as functional foods. This study analyses the potential of plants kept in the collections of BBG as functional foods and medicine sources with nutritional and health values. Literature studies have been carried out related to nutrition value and active substances owned by these plants, while data related to health claim was based on the results of ethnobotany studies, especially the use of medicinal plants by 28 ethnics in Indonesia. The results suggest 168 species of the BBG collection which can be claimed as a source of functional food which can be categorized into seven main categories. Among these plants are species classified as threatened or endangered such as Mangifera casturi, Vanilla planifolia, Pterocarpus indicus, Borassus flabellifer, Cycas rumphii, Dillenia philippinensis, and Litchi chinensis. Key words: BBG, functional food, threatened species